22‐gauge fine‐needle biopsy needles: Primary workhorse for endoscopic ultrasound‐guided tissue acquisition. Issue 3 (29th November 2021) - Bang, Ji Young; Varadarajulu, Shyam
Abstract : This Editorial refers to the article by T. Tomoda et al., p 596‐603 of this issue.